Impactos dos sistemas de produção e debicagem na produção e qualidade de ovos de poedeiras - Kuhn, Micheli Faccin (2019)
The production of eggs in conventional cages has been strongly questioned as to the welfare provided to the animals; this system could cause physical discomfort and inhibit the manifestation of natural behaviors. In this way alternative systems have emerged, which aim to improve the welfare of animals in the production system. Faced with this, one of the major challenges is to establish which of the production systems provides an adequate level of animal welfare, since no system meets all welfare requirements unless the animal is in freedom. The experiment was conducted in two experimental aviaries located in the Poultry Laboratory of the Federal University of Santa Maria. The objective of this study was to compare the performance and egg quality of laying hens, housed in conventional cages and in a floor (wood shaving was used as litter). The experiment used a total of 528 laying hens, Isa Brown line, 21 weeks old, distributed in a completely randomized design, with 4 treatments in a 2 x 2 factorial scheme (2 housing systems x 2 types of beak trimming), with 6 replicates of 22 birds each. The birds were divided into two groups, maintained in different housing systems (conventional cage versus floor with wood shaving litter), productive performance was counted daily from 21 to 40 weeks. This period was divided in five periods of 28 days each; period I (21st – 24th wks of age), II (25th – 28th wks of age), III (29th – 32nd wks of age), IV (33rd – 36th wks of age) and V (37th – 40th wks of age). The birds kept on the ground had better egg laying rates in periods I, II, III and IV and had heavier eggs in all periods than eggs produced by cage birds (P<0.0001). In all periods, it was observed that egg yolks had higher weights than the others (P<0.05). In periods I, II, III and IV, hens housed on the ground presented higher albumen weight (P<0.0001). The birds kept in the cage had worse warping conditions of the neck and tail regions (P<0.0001). The host system influenced the presence of intestinal parasites of the genus Raillietina, where it was observed that birds housed in the ground had a high incidence of them (P<0.0001). Birds kept in different productive systems and beak trimming did not have foot lesions (P>0.05). The debiting did not influence egg quality (P>0.05). Birds free of cages produced more eggs. Birds submitted to different systems and beak trimming produced eggs of the same quality. The housing system had no effect on contamination by Salmonella spp., Enterobacteria and total coliforms. The cage - free birds presented parasitic contamination with helminths of the genus Raillietina.